Etymological observations concerning the name of the ancient city of Chan Chan and its architectonic structures - Urban, Matthias (2017)
This article provides onomastic and etymological comments regarding the prehispanic city of Chan Chan on the north coast of Peru. The article focusses specifi cally on the partially competing names of Chan Chan and Chimor, which are discussed under formal, semantic, and etymological aspects. Then, to the extent possible, the article also considers a possible name for an architectonic structure found within the urban complex.